2021
DOI: 10.1177/18344909211046646
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 conspiracy theories and compliance with governmental restrictions: The mediating roles of anger, anxiety, and hope

Abstract: The COVID-19 pandemic has been an ideal breeding ground for conspiracy theories. Yet, different beliefs could have different implications for individuals’ emotional responses, which in turn could relate to different behaviours and specifically to either a greater or lesser compliance with social distancing and health-protective measures. In the present research, we investigated the links between COVID-19 conspiracy beliefs, emotions (anger, anxiety, and hope), attitudes towards government restrictions, and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“… 3 Despite the evidence suggesting negative correlation between belief in conspiracy theory and support and/or compliance with governmental rule in the context of COVID-19 prevention, a few studies found different results. For example, Peitz et al, 2021 , conducting a study on a UK sample found that the relationship is not straightforward. The effect of believing in a conspiracy theory, depends on the emotion it evokes (e.g., while anger led to higher perceived importance of governmental restrictions, anxiety achieved just the opposite).…”
mentioning
confidence: 99%
“… 3 Despite the evidence suggesting negative correlation between belief in conspiracy theory and support and/or compliance with governmental rule in the context of COVID-19 prevention, a few studies found different results. For example, Peitz et al, 2021 , conducting a study on a UK sample found that the relationship is not straightforward. The effect of believing in a conspiracy theory, depends on the emotion it evokes (e.g., while anger led to higher perceived importance of governmental restrictions, anxiety achieved just the opposite).…”
mentioning
confidence: 99%
“…Accordingly, believing in conspiracy theories around COVID-19 is perceived to undermine institutional trust, governmental regulations support and its adoption, and social engagement, like helping members of risk groups (Pummerer et al, 2021). It has been seen to lower social distancing compliance and other measures of health protection, including vaccination and putting on masks (Peitz et al, 2021). Accepting conspiracy narratives can lead to the dismissal of credible scientific information by people as it minimises the perceived importance of engaging in collectively beneficial behaviours (Lewandowsky et al, 2013).…”
Section: Journal Of Policy and Development Studiesmentioning
confidence: 99%
“…Importantly, their findings suggest that active rejection of conspiracy theories and theorists may be a useful alternative to conceptualizing and examining the impact of conspiracy theories. Peitz et al (2021) examined the links between conspiracy beliefs and attitudes toward mandatory COVID-19 policies with self-reported compliance regarding social distancing and health-protection measures. In particular, they posited that COVID-19 conspiracy beliefs would relate to people's response to mandatory COVID-19 policies through differential emotional pathways.…”
Section: The Role Of Attitudes Toward Societal Systemsmentioning
confidence: 99%